ANTIHYPERTENSIVE THERAPY EFFECTIVENESS DEPENDING ON ADHERENCE TO TREATMENT IN OUTPATIENT PRACTICE IN PATIENTS WITH STAGE 1-2 ARTERIAL HYPERTENSION - Bilovol, O.M.; Kniazkova, I.I.; Golovachova, V.O.; Kuzminova, N.V.; Kіrienko, D.О.; Kіrienko, O.M.; Abramova, L.P. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the influence of antihypertensive therapy used in outpatient practice in patients with grade 1–2 arterial hypertension on parameters of central hemodynamics and organ protection in conditions of low adherence to treatment. The prospective study included 93 outpatients with newly diagnosed hypertension of grades 1–2 without a history of cardiovascular complications, including 49 men and 44 women (mean age 52.3±3.8 years). Depending on the prescribed antihypertensive therapy, the patients were divided into 3 groups: 1st – 15 patients who were prescribed monotherapy, 2nd – 40 – free combination and 3rd – 38 – fixed combination of two antihypertensive drugs. It was established that the appointment of patients with stage 1–2 hypertension in outpatient practice with antihypertensive therapy (monotherapy, various two-component combinations of antihypertensive drugs) for 6 months allowed achieving target blood pressure levels, which contributed to the improvement of left ventricular systolic function, a decrease in the degree of left ventricular hypertrophy and a nephroprotective effect. With low adherence of patients with stage 1–2 hypertension to treatment, the effectiveness of antihypertensive therapy and its cardioprotective and nephroprotective properties were significantly reduced. This indicates the significant relevance of determining adherence to treatment in real clinical practice, which will allow taking these provisions into account when drawing up programs of preventive measures to prevent cardiovascular complications in this cohort of patients.
Keywords: arterial hypertension; antihypertensive therapy; adherence to treatment; organ protection